Faktor- Faktor Yang Mempengaruhi Kepuasan Pengguna Dan Implikasinya Terhadap Kinerja Pengguna Sistem Informasi Akuntansi - Luluk Alfiani; Budi Septiawan; Sasa S. Suratman (Universitas Muhammadiyah Malang, 2022)
This study aims to determine whether there is an influence on the quality of accounting information systems, information quality and perceived usefulness on user satisfaction and their implications for individual performance at Perum BULOG West Java Regional Office. The research approach in this research is descriptive analysis and verification using primary data. The sampling technique used is probability sampling with simple random sampling technique. Statistical analysis used in this study is multiple linear regression analysis with hypothesis testing t test and f test. The number of population in this study was 64 people, the research sample used was 55 people with data sources obtained through the results of filling out questionnaires. The results show that the variables of accounting information system quality, information quality, perceived usefulness and user satisfaction have an effect on individual performance either partially or simultaneously. This study aims to determine what factors can improve the performance of users of accounting information systems. So, if in the end the users are satisfied and there is an increase in performance, then the company's performance will increase in line with the good performance of the users of the accounting information system.